APPLICATION OF THE PROGRAM-TARGET METHOD IN BUDGET MANAGEMENT - Prokopets, Liudmyla; Kantsur, Inna; Hats, Lyubov; Kharchenko, Tetiana; Smahlo, Olha (Бізнесу та управління персоналом, 2020)
Every country in the world is trying to plan optimally and distribute budget expenditures in the situation of modern market relations. They are doing this in order to achieve a balance between revenues and budget expenses. Each country needs to apply certain methods of budget management in order to achieve such goals. The program-targeted method of budget management deserves special attention. The aim of the article is to study the basic principles of application of the program-target method in budget management. Methods of scientific analysis and synthesis, abstraction and comparison are used to in order to reveal the basic principles of the program-target method in budget management. The methodological basis of the study is: Order of the Cabinet of Ministers of Ukraine "On approval of the Concept of application of the program-target method in the budget process"; Budget Code of Ukraine; data of Organization for Economic Cooperation and Development. According to the results of the disclosure of theoretical and practical principles of application of the program-target method in budget management, it is established that: the program-target method in the budget management is one of the most effectivemethods of budgeting; the practice of applying the program-target method in budget management is widespread in many countries, including Ukraine; program-target method in budget management is aimed at obtaining the expected results due to the rational distribution of expenses from the budget. It is determined that the key goal of introducing the program-target method in the practice of budget management in Ukraine is to determine the direct correlation between the funds allocated from the budget and the results obtained from the usage of such funds. The study found that in the process of applying the program-target method in budget management, such target indicators as cost indicators, product indicators, efficiency indicators and quality indicators are achieved. The analysis of the articles of the Budget Code of Ukraine revealed that budget programs, executors of budget programs, passports of budget programs and performance indicators from the implementation of budget programs are the components of the program-target method in budget management.
Keywords: Program-target method; Budgeting; State program; National budget; Local budget